Physiomorphic and molecular-based evaluation of wheat germplasm under drought and heat stress - Alsamadany, Hameed; Alzahrani, Yahya; Shah, Zahid Hussain (Frontiers in Plant Science, 2023)
Drought and heat stresses are potential problems reducing wheat yield particularly at terminal growth stages in arid and semiarid regions of the world. Current study intended to elucidate the impacts of individual and combined versions of drought and heat stresses on biochemical contents (antioxidant enzymes, proline, soluble proteins and soluble sugars), physiological parameters (chlorophyll, cell membrane stability, photosynthesis, stomatal conductance and transpiration), plant water relations (RWC, water potential, osmotic potential and pressure potential), agronomic traits (FLA, plant height, tillers plant-1, spike length, grains spike-1 andthousand grain weight) and genes expression (TaHSF1a, TaWRKY-33, TaNAC2L and TaGASR1) in four different thermostable and drought tolerant wheat genotypes (Gold-16, HS-240, Suntop, Hemai-13) collected from different countries. The experiment was conducted in two factorial arrangement using RCBD.The data for all traits except agronomic were collected at every fourth day since from initiation of stress till crop attained physiological maturity at reproductive stage. Besides, data collected were analyzed statistically using R-program and Statistix8.1. All traits depicted significantly high reduction except total soluble sugars, ψs, proline and cell membrane stability under both combined and individual treatments of drought and heat stresses. Furthermore correlation analysis revealed significant correlation between biochemical and physiological characteristics in determining crop agronomic productivity. Furthermore PCA and heatmap analysis confirmed association of traits strongly varied with type of stress and nature of wheat genotype.The SEM spectrographs and micrographs generated for the selected high and low tolerant samples revealed clear differences in mineral distribution and starch granulation.All genes showed comparatively highly relative expression under combined treatments of drought and heat stresses in all wheat genotypes but this expression was the highest in Gold-16 followed by HS-240, Suntop and Hemai-13. Overall, study concluded that plants are proactive entities and they respond to stresses at all levels; however the tolerant one have tendency to retain the integrity of biochemical, physiological and molecular equilibrium.